2014
DOI: 10.1111/nph.13183
|View full text |Cite
|
Sign up to set email alerts
|

Ancient horizontal transfer of transaldolase‐like protein gene and its role in plant vascular development

Abstract: A major event in land plant evolution is the origin of vascular tissues, which ensure the long-distance transport of water, nutrients and organic compounds. However, the molecular basis for the origin and evolution of plant vascular tissues remains largely unknown.Here, we investigate the evolution of the land plant TAL-type transaldolase (TAL) gene and its potential function in rice (Oryza sativa) based on phylogenetic analyses and transgenic experiments, respectively.TAL genes are only present in land plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Naturally produced recombinant DNA can result from: meiotic recombination; the action of diverse and often abundant mobile genetic elements; gene duplication; chromosomal inversions and translocations; novel gene assemblies; shuffling of exons and other gene fragments; chromosomal duplication; horizontal gene transfer; and incorporation of viral genes. In fact, all land plants appear to be "natural GMOs," as all contain genes apparently acquired horizontally [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]. To my knowledge, there is no published, validated research showing any fundamental biochemical or biophysical difference between DNA recombined in a test tube vs. that recombined in a living cell.…”
Section: Consumption Of Ge Cropsmentioning
confidence: 98%
“…Naturally produced recombinant DNA can result from: meiotic recombination; the action of diverse and often abundant mobile genetic elements; gene duplication; chromosomal inversions and translocations; novel gene assemblies; shuffling of exons and other gene fragments; chromosomal duplication; horizontal gene transfer; and incorporation of viral genes. In fact, all land plants appear to be "natural GMOs," as all contain genes apparently acquired horizontally [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194]. To my knowledge, there is no published, validated research showing any fundamental biochemical or biophysical difference between DNA recombined in a test tube vs. that recombined in a living cell.…”
Section: Consumption Of Ge Cropsmentioning
confidence: 98%
“…Caillau and Quick (2005) reported that TAL gene (ToTal1) accumulation has been observed in root, stem and red fruit of tomato. Another study by Yang et al (2014) showed that rice TAL was expressed in leaf, panicle, stem, knot, and root. A knockdown TAL plant using a genespecific RNA interference (RNAi) construct in rice, showed reduction of TAL transcript in leaves of TAL-RNAi line.…”
Section: Functional Annotation Of Selected Degsmentioning
confidence: 99%
“…A knockdown TAL plant using a genespecific RNA interference (RNAi) construct in rice, showed reduction of TAL transcript in leaves of TAL-RNAi line. They found that knockdown TAL gene leads to changes in number and pattern of vascular bundles (Yang et al, 2014). TAL up-regulation may enhance the flux to shikimate pathway (Misra et al, 2010) from primary to secondary metabolites enabling synthesis of aromatic amino acid, flavonoids, and lignin.…”
Section: Functional Annotation Of Selected Degsmentioning
confidence: 99%
“…For instance, the vein patterning 1 (VEP1) gene in land plants, presumably acquired from bacteria, is involved in vascular strand formation [33,39]. Most recently, Yang et al investigated the evolution of TAL-type transaldolase (TAL) gene and found that land plant TAL genes are derived from actinobacteria [40]. TAL is ubiquitous in land plants and positively selected [40].…”
Section: Hgt In Plant Colonization Of Landmentioning
confidence: 99%
“…Most recently, Yang et al investigated the evolution of TAL-type transaldolase (TAL) gene and found that land plant TAL genes are derived from actinobacteria [40]. TAL is ubiquitous in land plants and positively selected [40]. Transgenic experiments in rice showed that TAL is specifically expressed in vascular tissues.…”
Section: Hgt In Plant Colonization Of Landmentioning
confidence: 99%